Balancing Yield and Sustainability: A Comparative Analysis of Supplemental Lighting in Commercial-Scale Cucumber Cultivation - Seyed Mohammad Hashemi; Andrzej Kurenda; Selin Karatepe; Nick A. Savidov (Horticulturae)
Lighting is a fundamental driver of plant productivity in controlled-environment agriculture (CEA), directly affecting physiological processes, resource efficiency, and sustainability. This study evaluates the effects of distinct lighting systems, industrial Light-Emitting Diodes (iLEDs), horticultural LEDs (hLEDs), high-pressure sodium (HPS) lamps, and controls (no supplemental light), each providing unique light spectra, on cucumber (Cucumis sativus L.) growth, physiology, and environmental impact under a controlled light intensity of 250 µmol m−2 s−1 in a commercial CEA setup. The results indicated that iLEDs enhance intrinsic water use efficiency (35.65 µmol CO2/mol H2O) and reduce transpiration, reflecting superior physiological resource use. Electrophysiological measurements indicated significantly more stable stress responses in plants subjected to iLEDs and hLEDs as compared to HPS and control treatments, indicating the effectiveness of LED light spectra in mitigating stress-related physiological impacts. Furthermore, compact growth and shorter stem internodes were observed under iLEDs as well as hLEDs, highlighting the spectral effects on photomorphogenesis, likely caused by a balanced light spectrum. HPS lighting achieved the highest yield (42.86 kg m−2) but at a significant environmental cost, with 342.65 kg CO2e m−2 emissions compared to 204.29 kg CO2e m−2 for iLEDs, with competitive yield of 38.84 kg m−2. Economic analysis revealed that iLEDs also offered the most cost-effective solution due to lower energy consumption and extended lifespan. This study focused on the interaction between light spectra, photosynthetic performance, stress resilience, and resource efficiency, advancing sustainable strategies for energy-efficient food production in CEA systems.